A Lithosphere‐Asthenosphere Boundary and Partial Melt Estimated Using Marine Magnetotelluric Data at the Central Middle Atlantic Ridge. (14th September 2020) - Wang, Shunguo; Constable, Steven; Rychert, Catherine A.; Harmon, Nicholas
Abstract: The differential motion between the lithosphere and the asthenosphere is aseismic, so the magnetotelluric (MT) method plays an important role in studying the depth and nature of the lithosphere‐asthenosphere boundary (LAB). In March 2016, we deployed 39 marine MT instruments across the Middle Atlantic Ridge (MAR), 2, 000 km away from the African coast, to study the evolution of the LAB with ages out to 45 million years (My). The MT acquisition time was limited to about 60 days by battery life. After analyzing dimensionality and coast effects for the MT data, determinant data were inverted for two‐dimensional resistivity models along two profiles north and south of the Chain Fracture Zone (CFZ). The imaged thickness of the lithospheric lid (>100 Ωm) ranges from 20 to 80 km, generally thickening with age. In the north of CFZ, punctuated low‐resistivity anomalies (<1 Ωm), likely associated with potential partial melts, occur along its base. In the south of CFZ, the base of the resistive lid is demarcated by a low‐resistivity channel (<1 Ωm) most likely fed by deeper melts. Sensitivity analyses and structural recovery tests indicate the robustness of these features. Resistivity models are in good agreement with results of seismic data. These results imply that partial melt is persistent over geologic timescales and that the LAB is dynamic features fed by upward percolation of mantle melt. The melt fraction is about 1–7% based on the resistivity, temperature, pressure, and hydrous basalt models, which is consistent with petrophysical observations. Plain Language Summary: The magnetotelluric (MT) method, using natural electromagnetic (EM) fields variations caused by lighting/solar wind, is used to image the depth variation of the lithosphere‐asthenosphere boundary (LAB) out to 45 million years (My) at the Middle Atlantic Ridge (MAR). Young oceanic lithosphere is considered geologically simple compared with the continental lithosphere. In March 2016, we deployed 39 MT instruments at the seafloor of the MAR for about 60 days. The deployment was along two profiles (L1 and L2). We processed and analyzed the MT data, and then we inverted the data for electrical resistivity models. The robustness of the resistivity models was tested by various methods. The resistivity model along the L1 shows the depth of the LAB dips from 20 to 80 km as the lithosphere ages from 0 to 45 My. The resistivity model along the L2 shows a low‐resistivity channel, which demarcates the base of lithosphere. Other geophysical methods, such as seismic surface‐wave tomography and receiver function, agree with the MT results. Our models imply that the partial melt is persistent over geological timescales and the LAB can only be represented by a dynamic model. Melt fracture is estimated as 1–7% using the resistivity and available petrophysical models. Key Points: Marine magnetotelluric data are used to better understand the lithosphere‐asthenosphere boundary at the central Middle Atlantic Ridge A dynamic lithosphere‐asthenosphere boundary is observed and compatible with geodynamic modeling Partial melt fraction, 1–7%, is estimated based on the inverted resistivity models and consistent with previous studies